(untitled) (Fiep Bulletin - online, 2013)
This research aimed to evaluate, through psychomotor test, the psychomotor profile of children aged 3 to 5 years old who attend classes in ASKACE Kodomo - School of Shotokan Karate-do. a descriptive quantitative approach carried out with 14 children from the middle and upper middle classes in the city of Fortaleza, Brazil. In the study, was used as a research tool one Psychomotor Battery Adaptation (BPA) from the Psychomotor Battery (BPM) developed by Fonseca in 1995. 57% of the evaluated psychomotor profile presented Eupráxico, 36% showed a profile Hiperpráxico psychomotor, and 7% showed Dyspraxia. From the analysis of data on psychomotor tests, it was concluded that this population has a good psychomotor development.